The effect of mineral nutrition on the biochemical composition of Venyaminovskoe apple cultivar fruits - Vetrova Oksana; Makarkina Margarita; Larisa Leonteva (BIO Web of Conferences, 2022)
The results of a five-year study of the mineral fertilizers' effect on the chemical composition of Venyaminovskoe apple cultivar fruits are presented. It is shown that the use of soil and foliar application of nitrogen and potash fertilizers did not have a significant effect on the content of soluble solids, sugars, titrated acids, ascorbic acid, and phenolic compounds in fruits. It was established that the most significant factor affecting the chemical composition of fruits are the weather conditions of the growing season. At the same time, the content of ascorbic acid significantly exceeding the control over an average of five experimental years was found in the option with the introduction of nitrogen and potash fertilizers into the soil at a dose of N60K80 together with foliar top dressing. There is a tendency of increasing accumulation of leucoanthocyanins in fruits over the years. In 2021, there was a significant decrease in catechins with the use of mineral fertilizers at a dose of N60K80, as well as in the following options: without soil and minimal (N30K40) fertilization against the background of top dressing.